CCSP self-study : Cisco secure intrusion detection system (CSIDS) - Carter, Earl (Cisco Press, 2004)
Understand how Cisco IDS can be used to protect, monitor, and enforce physical security policies Review techniques applicable to both network- and host-based platforms Review the security wheel concepts and apply security to AVVID using the SAFE Blueprint Install and configure the Cisco IDS to monitor your network for malicious activity Understand Cisco Threat Response (CTR) benefits and how it operates Apply alarm signatures and gain the proficiency to create your own custom signatures Deploy Cisco IDS effectively in your network using sensor and management platforms Get inside the Cisco Security Agent (CSA) architecture In addition to firewalls and other security appliances intended to limit outsider access to a network, intrusion detection and targeted countermeasures are a critical component of a complete network security plan. The Cisco Intrusion Detection Sensors and Management options work as a united system to provide detection, notification, and aggressive lockdown to malicious network breaches. CCSP Self-Study: Cisco Secure Intrusion Detection System (CSIDS), Second Edition , offers in-depth configuration and deployment information for the reliable and intensive intrusion detection solutions from Cisco Systems. CCSP Self-Study: Cisco Secure Intrusion Detection System (CSIDS) , Second Edition, is a Cisco authorized, self-paced learning tool that helps you gain mastery over the use of both the host-based and network-based IDS options (as well as the Cisco Threat Response functionality) by presenting a consolidated all-inclusive reference on all of the current Cisco IDS sensor platforms and management platforms. Chapter overviews bring you quickly up to speed and help you get to work right away. Configuration examples are designed to show you how to make the most of your IDS system, and unique chapter-ending review questions test your knowledge. Whether you are seeking a reference guide to working with the CIDS sensor and management platforms or a study guide for the 642-531 exam, CCSP Self-Study: Cisco Secure Intrusion Detection System (CSIDS) , Second Edition, supports your effective use of the Cisco IDS. CCSP Self-Study: Cisco Secure Intrusion Detection System (CSIDS) , Second Edition, is part of a recommended learning path from Cisco Systems that can include simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press. To find out more about instructor-led training, e-learning, an...